2007
DOI: 10.1177/0010414007300694
|View full text |Cite
|
Sign up to set email alerts
|

Economic Origins of Electoral Support for Authoritarian Successors

Abstract: This study explores how economic performance prior to democratic transitions affects the fate of successors to authoritarian rulers in new democracies. It investigates 70 founding election outcomes, finding that successful economic performance under an authoritarian regime increases the vote share of successors. It also finds that the past economic performance of authoritarian rulers decreases the likelihood of government alternation to democratic oppositions. Interim governments that initiate democratic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Moreover, while most studies have investigated distributive politics within a democratic context (Golden and Min 2013) or a nondemocratic setting (Blaydes 2010;Magaloni 2006), our study evaluates long-term effects that cut across regime types. Adding to the cross-national studies showing the cross-regime effects of development policies (Jhee 2008;Miller 2021), this study provides microlevel evidence from subnational analyses over several decades. By illustrating the persistent long-term effect of a rural development program, we also contribute to the growing literature on authoritarian nostalgia in new democracies (Dinas and Northmore-Ball 2020;Neundorf, Gerschewski, and Olar 2020).…”
Section: Rural Development Program and Electionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, while most studies have investigated distributive politics within a democratic context (Golden and Min 2013) or a nondemocratic setting (Blaydes 2010;Magaloni 2006), our study evaluates long-term effects that cut across regime types. Adding to the cross-national studies showing the cross-regime effects of development policies (Jhee 2008;Miller 2021), this study provides microlevel evidence from subnational analyses over several decades. By illustrating the persistent long-term effect of a rural development program, we also contribute to the growing literature on authoritarian nostalgia in new democracies (Dinas and Northmore-Ball 2020;Neundorf, Gerschewski, and Olar 2020).…”
Section: Rural Development Program and Electionmentioning
confidence: 95%
“…Scholars have shown that an authoritarian past is not necessarily a burden to politicians or political parties after democratization but can actually function as an asset to build on (Albertus 2019; Loxton 2015; Miller 2021; Riedl 2014). Using cross‐country data from new democracies, Miller (2021) and Jhee (2008) find evidence that a policy success in the past—for example, an achievement in economic development—can provide an advantage to the authoritarian successor party. Pop‐Eleches and Tucker (2017) and Neundorf, Gerschewski, and Olar (2020) further argue that the legacy effect of a past dictatorship significantly affects individual voter preferences.…”
Section: Rural Development Program and Electionmentioning
confidence: 99%
“…It is this contrast between the past, as a period of possibility, and the present, as a period of dissatisfaction, that facilitates a longing for the former dictatorship. This discussion of economic aspects corresponds to prior work that emphasizes economic evaluation across regime types as a key source of nostalgia for the former dictatorship (Jhee 2008;Tucker 2006). Even younger interview participants, who did not enjoy economic prosperity under dictatorship, romanticized the more stable performance of the past as historical abstraction rather than personal memories (Marchegiani and Phau 2010).…”
Section: Economic Developmentmentioning
confidence: 62%
“…This is because authoritarian regimes tend to utilize nationalism, a key characteristic of blind national pride, to promote unconditional political support in facing the twin challenges of nation-building and industrialization (Dukalskis and Gerschewski 2017). Hence, when individuals shape their national sentiments via the socialization process under those circumstances (Neundorf and Pop-Eleches 2020) and, more importantly, when successor parties sustain the nationalist legacies even after democratization (Jhee 2008; Miller 2021), citizens in new democracies are likely to be active in political participation based on blind national pride. If such is the case, we expect the positive relationship to be more robust among older citizens, because they have experienced the authoritarian regime both recently and directly, which would lead them to have a stronger and better memory of it.…”
Section: Blind National Pride and Voter Turnout In New Democraciesmentioning
confidence: 99%